2018
DOI: 10.3390/membranes8040102
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polymer Electrolyte Membranes via Radiation-Induced Graft Copolymerization on Poly(ethylene-alt-tetrafluoroethylene) (ETFE) Using the Crosslinker N,N′-Methylenebis(acrylamide)

Abstract: Polymer electrolyte membranes (PEM) prepared by radiation-induced graft copolymerization are investigated. For this purpose, commercial poly(ethylene-alt-tetrafluoroethylene) (ETFE) films were activated by electron beam treatment and subsequently grafted with the monomers glycidyl methacrylate (GMA), hydroxyethyl methacrylate (HEMA) and N,N′-methylenebis(acrylamide) (MBAA) as crosslinker. The target is to achieve a high degree of grafting (DG) and high proton conductivity. To evaluate the electrochemical perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Previously, graft copolymerization on ETFE after pre-activation via EB treatment was studied in detail [39,44]. It was shown that EB doses ranging from 40 to 100 kGy in the activation step are well suited to achieve high degrees of branching ( DG ) and very good proton conductivity of the PEMs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, graft copolymerization on ETFE after pre-activation via EB treatment was studied in detail [39,44]. It was shown that EB doses ranging from 40 to 100 kGy in the activation step are well suited to achieve high degrees of branching ( DG ) and very good proton conductivity of the PEMs.…”
Section: Resultsmentioning
confidence: 99%
“…%. Higher monomer fractions are not feasible, since polymerization may occur in the liquid phase due to transfer of radicals to the monomers or solvent leading to polymerization in the reaction mixture [44]. DG increased from 28% to 1335% and the conductivity from 0.3 to 93.5 mS∙cm −1 in going from 10 to 30 vol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations